Helical folding in heterogeneous foldamers without inter-residual backbone hydrogen-bonding - Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Mishra, Deepti; Pal, Sourav; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
This communication describes a set of hybrid foldamers that do not feature inter-residual, but intra-residual backbone hydrogen-bonding, yet adopt a preferentially folded conformation displaying right-handed helical architecture. Conformational ordering is apparently due to the combined conformational restrictions imposed by the conformationally restricted individual amino acid residues with which the oligomers are made of.